"Sensors Everywhere!": The history of industry's first fiber Bragg grating manufacturing system and subsequent sensors development. Issue 6 (14th November 2019) - Pozo, Jose
Abstract: In this article, Jose Pozo, EPIC's CTO talks to Remco Nieuwland. Remco is the mind and soul behind the development of the NORIA system: the first world‐wide tool to manufacture fiber Bragg gratings. Remco is now CTO of Somni Solutions, a Dutch company that designs, develops and manufactures high‐end fiber optic sensors and sensor systems.